Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Driving Experience on Change Detection Based on Target Relevance and Size

Abstract: Summary:Earlier studies that investigated the effects of driving experience and target safety relevance on change detection have produced conflicting results. Using a flicker change detection task to investigate the effect of driving experience on the ability to detect changes in objects that vary in safety relevance and size, the present study attempted to clarify some controversies by addressing three important methodological issues. The data showed that experienced drivers exhibited more efficient selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…RT to correctly identify changes followed a similar pattern, with faster responses to non-sign change targets. Many previous studies examining the effect of change target compared relevant versus irrelevant targets (e.g., Galpin et al, 2009;Mueller and Trick, 2013;Zhao et al, 2014), whereas in the current study we found marked differences in change blindness towards different types of driving-related targets. All observers were more likely to experience change blindness when the target that was moved or removed was a road sign, and were slower to notice the changes that they did identify.…”
Section: Effects Of Change Target and Typecontrasting
confidence: 80%
See 2 more Smart Citations
“…RT to correctly identify changes followed a similar pattern, with faster responses to non-sign change targets. Many previous studies examining the effect of change target compared relevant versus irrelevant targets (e.g., Galpin et al, 2009;Mueller and Trick, 2013;Zhao et al, 2014), whereas in the current study we found marked differences in change blindness towards different types of driving-related targets. All observers were more likely to experience change blindness when the target that was moved or removed was a road sign, and were slower to notice the changes that they did identify.…”
Section: Effects Of Change Target and Typecontrasting
confidence: 80%
“…Observers with domain expertise are more efficient than domain-novices at detecting changes, but only when the changes are relevant to their expertise (Feil and Mestre, 2010;Reingold et al, 2001;Werner and Thies, 2000). In contrast, bottom-up salience and physical size do not influence change detection in real-world contexts, including driving-related tasks (Caird et al, 2005;Mueller and Trick, 2013;Richard et al, 2002;Stirk and Underwood, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various driver characteristics were analysed in different environments, to understand behavioural patterns of drivers in general. One of the features analyzed was the factor of experience in driving [7] . The study aims to further understand while driving, how different object size and shape (along the course) serve as qualifiers as to what is relevant to the driver and what isn't.…”
Section: Experiments Conducted and Results Obtainedmentioning
confidence: 99%